Process for Simultaneous Removal of S8, DBDS, and PCBs From Mineral Insulating Oils - Dejan M. Kolarski; Jelena M. Lukic; Jelena U. Jankovic; Sandra B. Glisic; Aleksandar M. Orlovic (IEEE Access, 2025)
The presence of corrosive sulfur and polychlorinated biphenyls (PCBs) in mineral insulating oils poses significant challenge to the reliability of power transformers and presents serious environmental risks. Elemental sulfur (S8) and dibenzyl disulfide (DBDS) are well-known for causing the formation of metal sulfides on transformer components, leading to equipment failures, while PCBs present in insulating oils are persistent environmental pollutants with long-term health hazards. Current insulating oil purification techniques, including adsorbents, metal passivators and reagents, exhibit limited effectiveness, particularly if elemental sulfur is present in oil. This study introduces a novel reagent-based desulfurization process which uses copper deposited on iron particles dispersed in polyethylene glycol, for the complete removal of S8 from mineral insulating oil. The integration of S8 removal process with the KOH/PEG complex enables the simultaneous removal of S8, DBDS, and PCBs, with no residual metal particles detected in the oil following the treatment. Laboratory-scale experiments have shown the high efficiency of the developed process resulting in the improved physical-chemical and electrical properties of the oil, which was further verified on pilot scale unit and finally on the industrial scale process unit.